2006
DOI: 10.1111/j.1746-1049.2006.00013.x
|View full text |Cite
|
Sign up to set email alerts
|

Productivity Impact of the Modern Varieties of Rice in India

Abstract: The present paper analyzed the long‐term yield growth and total factor productivity (TFP) growth by applying Tornqvist‐Theil index method for two periods, namely, 1970–85 (early Green Revolution) and 1986–2000 (late Green Revolution), for major rice‐growing states of India. The yield data shows an increasing long‐term growth trend throughout the Green Revolution period in irrigated states where modern variety (MV) adoption was nearly complete. However, yield advances started to slow down for intensive irrigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 12 publications
(4 reference statements)
3
20
1
Order By: Relevance
“…For m = 1 also, the predicted irrigation effect hits its peak in 1985. These results clearly suggest that early generations of rice technology require more irrigation than do recent ones, which is consistent with the descriptive analysis of MV adoption by Janaiah, Hossain and Otsuka (2006) and Byerlee (1996). Also, it is confirmed that irrigation works to reduce the impact of temperature and rainfall.…”
Section: Ricesupporting
confidence: 78%
See 1 more Smart Citation
“…For m = 1 also, the predicted irrigation effect hits its peak in 1985. These results clearly suggest that early generations of rice technology require more irrigation than do recent ones, which is consistent with the descriptive analysis of MV adoption by Janaiah, Hossain and Otsuka (2006) and Byerlee (1996). Also, it is confirmed that irrigation works to reduce the impact of temperature and rainfall.…”
Section: Ricesupporting
confidence: 78%
“…In the early GR period (1974 to 1988), the correlation coefficients are high for wheat, rice, and maize at 0.76, 0.79, and 0.62 respectively, while they are only 0.38, 0.35, and 0.46 in the subsequent period (1989 to 2002). In fact, such a trend is consistent with the preceding studies by Janaiah et al (2006), Gollin (2006), and Byerlee (1996), all of which point out that the MVs released in the earlier period were high-yielding only under favorable production environments, whereas subsequent generations of MVs possess traits suitable for a variety of agro-climates. Given these changing correlation coefficients, we attempt to find out the impact of technology on the climate effects by regarding the district-level irrigation variable as a district-level technology indicator, which is expected to capture the compound effects of irrigation and MV technology only in the early stage of the GR for wheat, rice, and maize.…”
Section: Introduction Of the Issuesupporting
confidence: 79%
“…1 See for the case of India: Bhushan (2005), Dholakia and Dholakia (1993), Evenson et al (1999), Evenson and McKin (1991), Fan et al (1999), Janaiah et al (2006, Kaur and Sekhon (2005), Kumar et al (2004), Mahadevan (2003), Murgai (2001), Roy and Pal (2002), Upender (2005).…”
mentioning
confidence: 97%
“…The rainfed region of Eastern India was estimated to be important in driving overall trends toward MV adoption, accounting for nearly a third of total MV adoption (Janaiah et al, 2006) in Assam, Bihar, Madhya Pradesh and West Bengal. The study covered the states of Assam, Bihar, Madhya Pradesh and West Bengal, and found that each area experienced significant jumps in rice yields during the 1980s.…”
Section: Sustainability Of Rainfed Rice Agriculture In India: a Litermentioning
confidence: 99%